The Role of Indonesian Muslim Student Action Unit (KAMMI) as Election Monitors in Improving Supervisory Integrity in the 2019 General Election in the City of Banjarmasin - Alfikri (Sharia Journal and Education Center Publishing, 2024)
ABSTRACT This research was conducted in Banjarmasin City against the backdrop of the large number of election violations and the large number of polling stations that must be monitored in the 2019 elections in Banjarmasin City. KAMMI as an election monitor involves itself in this supervision so that the election runs in accordance with the principles of the election. Election monitors can detect potential violations, provide confidence to the public regarding the validity of the results, and encourage accountability of election organizers. The existence of election monitors is also a form of social control that helps strengthen the foundations of democracy and increase active citizen participation in elections. This study aims to determine the role of the Indonesian Muslim Student Action Unit (KAMMI) as an election monitor in improving the integrity of supervision in the 2019 elections in Banjarmasin City, then to find out how the obstacles were faced. The type of research used is field research, by examining the circumstances and phenomena more clearly about the situation that occurs in the field. The research approach is a qualitative approach with qualitative descriptive methods. Data sources are informants totaling 9 people and documentation. Analysis of the results of this study was carried out by analyzing the data collected and presented in the form of descriptive descriptions. Then the researcher makes a conclusion and recommendation on the research results. The results showed that KAMMI played an adequate role as an extension of Bawaslu in monitoring the 2019 elections in Banjarmasin City. KAMMI carries out its duties according to the rules and code of ethics, is neutral, provides education to the public, and supports the participation of persons with disabilities. KAMMI faces obstacles in monitoring the 2019 elections in Banjarmasin City, including limited number of members, unstructured programs, and limited funds. Other internal factors include the focus of monitoring only on election day. External constraints include a lack of cooperation with Bawaslu Banjarmasin City, a lack of coordination between South Kalimantan Province Bawaslu and Banjarmasin City Bawaslu, and an unstructured coordination schedule. Despite the obstacles, KAMMI managed to improve the integrity of election monitoring. KAMMI's involvement as a political monitor can be a motivation for other institutions, although improvements are needed to overcome obstacles in the future. Keywords: KAMMI, Election Monitoring, Surveillance. ABSTRAK Penelitian ini dilakukan di Kota Banjarmasin dengan dilatarbelakangi masih banyaknya pelanggaran Pemilu dan banyaknya TPS yang harus di awasi pada Pemilu tahun 2019 di Kota Banjarmasin. KAMMI sebagai pemantau Pemilu melibatkan diri dalam pengawasan tersebut agar Pemilu berjalan sesuai dengan prinsip-prinsip Pemilu. Pemantau pemilu dapat mendeteksi potensi pelanggaran, memberikan keyakinan kepada masyarakat terkait keabsahan hasil, serta mendorong akuntabilitas penyelenggara Pemilu. Keberadaan pemantau Pemilu juga menjadi bentuk kontrol sosial yang membantu memperkuat fondasi demokrasi dan meningkatkan partisipasi aktif warga negara dalam pemilihan umum. Penelitian ini bertujuan untuk mengetahui peran Kesatuan Aksi Mahasiswa Muslim Indonesia (KAMMI) sebagai pemantau Pemilu dalam meningkatkan integritas pengawasan pada Pemilu tahun 2019 di Kota Banjarmasin, kemudian untuk mengetahui bagaimana kendala yang dihadapi. Jenis penelitian yang digunakan adalah penelitian lapangan (field research), dengan meneliti keadaan serta fenomena lebih jelas mengenai situasi yang terjadi dilapangan. Pendekatan penelitian yaitu pendekatan kualitatif dengan metode deskriftif kualitatif. Sumber data berupa informan yang berjumlah 9 orang dan dokumentasi. Analisis hasil penelitian ini dilakukan dengan cara menganalisis data yang terkumpul dan disajikan dalam bentuk uraian-uraian secara deskriptif. Kemudian peneliti membuat suatu kesimpulan dan rekomendasi terhadap hasil penelitian. Hasil penelitian menunjukkan bahwa KAMMI cukup berperan sebagai perpanjangan tangan Bawaslu dalam pengawasan Pemilu 2019 di Kota Banjarmasin. KAMMI menjalankan tugasnya sesuai aturan dan kode etik, bersikap netral, memberikan edukasi kepada masyarakat, dan mendukung partisipasi penyandang disabilitas. KAMMI menghadapi kendala dalam pemantauan Pemilu 2019 di Kota Banjarmasin, termasuk jumlah anggota terbatas, program tidak terstruktur, dan dana terbatas. Faktor internal lainnya meliputi fokus pemantauan hanya pada hari pemilihan. Kendala eksternal mencakup kurangnya kerja sama dengan Bawaslu Kota Banjarmasin, kurangnya koordinasi antara Bawaslu Provinsi Kalimantan Selatan dan Bawaslu Kota Banjarmasin, serta jadwal koordinasi yang tidak terstruktur. Meskipun menghadapi kendala, KAMMI berhasil meningkatkan integritas pengawasan Pemilu. Keterlibatan KAMMI sebagai pemantau politik dapat menjadi motivasi bagi lembaga lain, meski diperlukan pembenahan untuk mengatasi kendala di masa depan. Kata Kunci: KAMMI, Pemantau Pemilu, Pengawasan.